Model and methods for protection of structured social group from negative information-psychological impact - Шиян, Анатолій Антонович; Яремчук, Юрій Євгенович (Ukrainian Information Security Research Journal, 2015)
Structured social group (SSG) is highlighted as a particularobject of investigation due to the fact that they are themost vulnerable targets for the realization of negativeinformation-psychological impact. The SSG operates as apowerful amplifier for information-psychological impact,which took place on its senior management. A modeltakes into account the hierarchical structure for SSG’sactivity. In such SSG people are divided into twocategories: coordinators (who can create new informationfor SSG or adequately restore it) and replicator (whichcan pass the information, at best, without distortion). Thisleads to the fact that the quantity of people in each higherhierarchical level is about 6% from the quantity of peoplein the lower level. Methods for SSG protection fromnegative information-psychological impact, which takeinto account their specific features, are developed. Amongthese are: the economic activities of organizations,activities of public institutions, the heterarchy of SSGstructure, the time frame of human functioning as acoordinator in SSG, limiting for democracy etc.